2014
DOI: 10.12688/f1000research.3-8.v2
|View full text |Cite
|
Sign up to set email alerts
|

Validation of predicted mRNA splicing mutations using high-throughput transcriptome data

Abstract: Interpretation of variants present in complete genomes or exomes reveals numerous sequence changes, only a fraction of which are likely to be pathogenic. Mutations have been traditionally inferred from allele frequencies and inheritance patterns in such data. Variants predicted to alter mRNA splicing can be validated by manual inspection of transcriptome sequencing data, however this approach is intractable for large datasets. These abnormal mRNA splicing patterns are characterized by reads demonstrating eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Hollestelle et al. [] argue that a more stringent statistical standard must be applied (i.e., P ‐values of 0.01 should be used as opposed to 0.05) to underreported variants (namely in moderate‐risk alleles), because of failure to replicate pathogenic variants, which we have also found [Viner et al., ]. In the same way that we use IT‐based analysis to justify prioritizing variants for further investigation, variants that are disregarded as lower priority (and that are likely not disease causing) have been subjected to the same thresholds and criteria.…”
Section: Discussionmentioning
confidence: 67%
“…Hollestelle et al. [] argue that a more stringent statistical standard must be applied (i.e., P ‐values of 0.01 should be used as opposed to 0.05) to underreported variants (namely in moderate‐risk alleles), because of failure to replicate pathogenic variants, which we have also found [Viner et al., ]. In the same way that we use IT‐based analysis to justify prioritizing variants for further investigation, variants that are disregarded as lower priority (and that are likely not disease causing) have been subjected to the same thresholds and criteria.…”
Section: Discussionmentioning
confidence: 67%
“…Exon-based expression microarrays and q-RT-PCR techniques were initially used to confirm the predicted impact of common and rare SNPs on splicing. Results were subsequently confirmed using RNAseq data for some of these SNPs (Dorman et al, 2014;Viner et al, 2014;Shirley et al, 2019). However, exon skipping due to rs1893592 was not consistently seen in all carriers.…”
Section: Discussionmentioning
confidence: 82%
“…This facilitates prediction of phenotypic severity (Rogan and Schneider, 1995;von Kodolitsch et al, 1999;von Kodolitsch et al, 2006). The effects of splicing mutations can be predicted in silico by information theory (Rogan and Schneider, 1995;Kannabiran et al, 1998;Rogan et al, 1998;Svojanovsky et al, 2000;Rogan et al, 2003;Caminsky et al, 2014;Dorman et al, 2014;Viner et al, 2014;Caminsky et al, 2016;Mucaki et al, 2016;Shirley et al, 2019), and these predictions can be confirmed by in vitro experimental studies (Vockley et al, 2000;Lamba et al, 2003;Rogan et al, 2003;Khan et al, 2004;Susani et al, 2004;Hobson et al, 2006;Caux-Moncoutier et al, 2009;Olsen et al, 2014;Vemula et al, 2014;Peterlongo et al, 2015). Strengths of one or more splice sites may be altered and, in some instances, concomitant with amino acid changes in coding sequences (Rogan et al, 1998;Peterlongo et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…separate transfections on different weeks) were converted to log‐ratios for calculation of averages and standard errors for each variant. This log transformation was sufficient to produce approximately normally distributed ratios in this dataset with relatively large read counts (not shown); however for a dataset with small read counts, a transformation of the counts would be required (Viner, Dorman, Shirley, & Rogan, ).…”
Section: Methodsmentioning
confidence: 99%